In vitro induction and investigation of salinity tolerance in the callus of Vigna spp. (L) - Alsewidi, Wasan Mohammed; Al-Oubaidi, Hashim Kadhim (Edelweiss Applied Science and Technology, 2024)
Cowpeas can be employed for rotational grazing or generating high-quality food when paired with crops such as maize. Cowpea seeds provide a substantial amount of protein and other essential elements. The purpose of this work was to use a mutagen and a high salt concentration to extract a salt tolerance gene from the callus. The callus was induced by adding 2,4-Dichlorophenoxyacetic acid 2,4- D at mg/l and was then subjected to various concentrations of a combination of salts consisting of sodium chloride NaCl and Calcium Chloride.CaCl2, in addition to Magnesium chloride MgCl2, with a rate of 2:2:1 and potion 0, 50, 100, 150, 200, and 250 mM of the salt mixture added to the culture medium. Various levels of di ethyl sulfate (DES) mutagenic solution at a concentration of 0.1 mM were used to soak the callus for 30 minutes. The results showed that when using quantitative polymerase chain reaction q-PCR, they showed two genes of vigna, the first gene in this research. Aldehyde dehydrogenase family 3 (ADF3) demonstrated the explanation of the genes at doses of DES+200, 200, and 250 mM; however, the most elevated level of gene expression at DES+200mM is CT 30.47, with an upregulation of 2.479. The second gene, Protein S2, demonstrated that the gene is highly expressed at DES+200mM, cycle threshold (CT) 31.68, and DES+250mM concentrations and is upregulated at DES+150mM was 128.